Editorial - Grilli, Matteo (Southern Journal for Contemporary History, 2021)
Starting with this issue, I assume the editorship of the Southern Journal for Contemporary History, known until 2019 as the Journal for Contemporary History. This is a great honour for me. First, this is a historical journal that, since 1975, has been an essential instrument for academic debate in South Africa and beyond. Second, my tenure follows a few years of intense and exciting changes in the structure and purpose of the journal. I followed these changes with much interest, and I wish to build on the foundations laid by my predecessor, Professor Neil Roos, who re-imagined this publication.